Genetically modified attenuated salmonid alphavirus: A potential strategy for immunization of Atlantic salmon. Issue 7 (16th February 2021) - Aksnes, Ida; Braaen, Stine; Markussen, Turhan; Åkesson, Caroline Piercey; Villoing, Stephane; Rimstad, Espen
Abstract: Pancreas disease (PD) is a serious challenge in European salmonid aquaculture caused by salmonid alphavirus (SAV). In this study, we report the effect of immunization of Atlantic salmon with three attenuated infectious SAV3 strains with targeted mutations in a glycosylation site of the envelope E2 protein and/or in a nuclear localization signal in the capsid protein. In a pilot experiment, it was shown that the mutated viral strains replicated in fish, transmitted to naïve cohabitants and that the transmission had not altered the sequences. In the main experiment, the fish were immunized with the strains and challenged with SAV3 eight weeks after immunization. Immunization resulted in infection both in injected fish and 2 weeks later in the cohabitant fish, followed by a persistent but declining load of the mutated virus variants in the hearts. The immunized fish developed clinical signs and pathology consistent with PD prior to challenge. However, fish injected with the virus mutated in both E2 and capsid showed little clinical signs and had higher average weight gain than the groups immunized with the single mutated variants. The SAV strain used for challenge was not detected in the immunized fish indicating that these fish were protected against superinfection with SAV during the 12 weeks of the experiment.